A micro-nano gel plugging agent and its preparation method and micro-nano gel plugging slurry

By using acrylamide, crosslinking agent, polyvinyl alcohol, chitosan and other materials for supramolecular modification in the leak plugging agent, a water-soluble polymer with an orderly structure is formed, which solves the problem that the existing leak plugging agent cannot stop in the leak layer and low pressure bearing, and achieves efficient leak layer sealing and pressure bearing effect.

CN116162249BActive Publication Date: 2025-03-14CHINA NAT PETROLEUM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111412739.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-25
Publication Date
2025-03-14
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

The existing leak plugging agent cannot stop in the leaking layer, and is easily diluted by water mixing, and is difficult to retain and accumulate near the inlet of the leaking layer, and it is difficult to block the leaking channel, and it is difficult to form a stable pressure-bearing sealing layer on the smooth crack wall, with low bearing pressure.

Method used

The reverse-phase emulsion polymerization is carried out using acrylamide and crosslinking agent to form crosslinked microspheres, and the surface of the gel microspheres is modified by polyvinyl alcohol and chitosan to form a water-soluble polymer with an ordered supramolecular structure. The uniqueness of supramolecular chemical materials and the strong interaction with the leakage formation are used to increase the sealing effect.

Benefits of technology

It realizes effective retention and accumulation of micro-nanogel leak plugging agent in the leak layer, can stably seal the leaking channel, improve the pressure bearing capacity of the formation, the temperature resistance can reach 150℃, the pressure bearing reach 7.5MPa, and the construction is simple and the risk is low, which is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116162249B_ABST
    Figure CN116162249B_ABST
Patent Text Reader

Abstract

The present invention provides a micro-nano gel plugging agent and a preparation method thereof and a micro-nano gel plugging slurry, wherein the preparation method comprises: S1 mixing white oil and an emulsifier to obtain a mixed solution 1; S2 mixing water, a monomer and a cross-linking agent uniformly, adding an initiator, and mixing uniformly again to obtain a mixed solution 2; S3 mixing the mixed solution 2 and the mixed solution 1 uniformly under a nitrogen atmosphere, heating to 55-65° C., reacting for 1-2 hours, and obtaining a primary polymerization product; S4 dissolving polyvinyl alcohol and chitosan in water, adding them to the primary polymerization product, heating to 65-75° C., reacting for 12-36 hours, filtering, separating, purifying and drying to obtain a micro-nano gel plugging agent. The present invention is based on supramolecular chemistry theory, inserting special functional groups into macromolecules, and forming an ordered supramolecular structure, which can quickly form a grid structure, cement the surrounding medium into a solid whole in the leakage layer, and injecting a chemical plugging agent into the leakage layer to form a gel to block the leakage channel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum drilling fluids, and in particular relates to a micro-nano gel plugging agent and a preparation method thereof, and a micro-nano gel plugging slurry. Background Art

[0002] During the drilling process, well leakage is very common in complex formations such as caves and large cracks in mountainous and plateau areas, causing serious economic losses to drilling operations. In response to shallow, low-temperature, and large cave leakage, R&D personnel have explored different series of plugging materials and plugging technologies.

[0003] Conventional plugging technologies are mainly divided into two categories: static plugging methods and methods for dealing with well leakage in special and complex situations. Static plugging methods include: plugging with granular plugging materials, plugging with granular plugging agents and accelerator cement, MTC plugging methods, and high expansion network solidification plugging technology. Methods for dealing with well leakage in special and complex situations include: plugging of leakage in extra-large caves and cracks, plugging of leakage in water layers, plugging of leakage in water layers, plugging of leakage in multi-pressure layers, leakage in abnormal pressure zones, and leakage in the bottom layer of salt layers.

[0004] Commonly used plugging materials can be divided into six categories according to their mechanism of action and function, including bridging plugging materials, high water loss plugging materials, temporary plugging materials for reservoir protection, chemical plugging materials, inorganic gelling plugging materials and soft (hard) plugging materials. Among them, chemical gel, as a kind of chemical plugging material, has been increasingly valued due to its convenience and simple operation.

[0005] Micro-nano gel plugging agent is a fluid without solid phase. There is no problem of matching solid particles with the size and shape of the pores or cracks in the leakage layer. It is easy to enter the complex leakage channel and complete the plugging of different leakage layers, so it can plug multiple leakage layers at one time.

[0006] However, the current plugging drilling fluid technology still has the following problems: it cannot stay in the leaking layer, is easily diluted by water mixing, is difficult to accumulate near the entrance of the leaking layer, and is difficult to plug the leakage channel; it is difficult to form a stable pressure-bearing plugging layer on the smooth crack wall, and the bearing pressure is low. Summary of the invention

[0007] In order to overcome the shortcomings of the current plugging technology, the existing plugging agents cannot stay in the leaking layer, are easily diluted by water, are difficult to accumulate near the entrance of the leaking layer, and are difficult to block the leakage channel. At the same time, a pressure-bearing plugging technology that adapts to and meets the needs of different types of leaking layers is created to greatly improve the pressure-bearing capacity of the formation. The first purpose of the present invention is to provide a micro-nano gel plugging agent; the second purpose is to provide a preparation method of the micro-nano gel plugging agent; the third purpose is to provide a micro-nano gel plugging slurry.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a micro-nano gel plugging agent comprises the following steps:

[0010] S1, mixing white oil and emulsifier to obtain mixed solution 1;

[0011] S2, after mixing water, monomer and cross-linking agent evenly, adding initiator, and mixing evenly again to obtain mixed solution 2;

[0012] S3, under a nitrogen atmosphere, mixing the mixed solution 2 and the mixed solution 1, raising the temperature to 55-65° C., reacting for 1-2 hours, to obtain a primary polymerization product;

[0013] S4, dissolving polyvinyl alcohol and chitosan in water, adding them to the above-mentioned primary polymerization product, heating to 65-75° C., reacting for 12-36 hours, filtering, separating, purifying and drying to obtain a micro-nano gel plugging agent.

[0014] Furthermore, in step S1, the mass ratio of the white oil to the emulsifier is 1:(1-2), and the emulsifier is a Span emulsifier.

[0015] Furthermore, in step S2, the mass ratio of water, monomer and cross-linking agent is (10-20): (10-20): (0.2-1); the amount of initiator added is 1‰-2‰ of the mass of the monomer;

[0016] Furthermore, the monomer is acrylamide, the crosslinking agent is selected from at least one of divinylbenzene, N,N′-methylenebisacrylamide, N,N′-methylenebismethacrylamide, polyethylene glycol diacrylate, and pentaerythritol triacrylate; and the initiator is any one of ammonium persulfate, potassium persulfate, and sodium persulfate.

[0017] Furthermore, the mass ratio of the white oil in step S1 to the water in step S2 is 1:(10-20).

[0018] Furthermore, in step S4, the reaction time is 12 to 36 hours; preferably, the reaction time is 24 hours.

[0019] Furthermore, the mass ratio of the polyvinyl alcohol, chitosan and water is (1-3):(0.5-1):1.

[0020] Preferably, the molecular weight of the polyvinyl alcohol is 25,000 to 35,000.

[0021] A micro-nano gel plugging agent is prepared by the preparation method of the micro-nano gel plugging agent.

[0022] A micro-nano gel plugging slurry comprises a micro-nano gel plugging agent, a structural agent and water. The amount of the structural agent is 8-18% of the mass of the micro-nano gel plugging agent, and the amount of water depends on the concentration of the nano gel plugging liquid.

[0023] Furthermore, the structural agent is formed by mixing rigid particles, variable particles and mineral fibers in a mass ratio of (45-55): (25-35): (15-25).

[0024] By adopting the above technical solution, the present invention has the following beneficial effects:

[0025] 1. The preparation method of the micro-nano gel plugging agent proposed by the present invention uses acrylamide, a cross-linking agent, polyvinyl alcohol and chitosan as raw materials. First, acrylamide and a cross-linking agent are used for reverse emulsion polymerization to form cross-linked microspheres. Then, polyvinyl alcohol and chitosan are used to modify the surface of the microspheres to synthesize polyacrylamide microspheres modified with polyvinyl alcohol and chitosan. Since polyvinyl alcohol and chitosan are both macromolecules with a large number of hydroxyl groups on the surface, polyvinyl alcohol and chitosan are introduced in the later stage of the reaction. By wrapping and modifying the surface of the gel microspheres, a large number of hydrogen bonds are added to the surface of the gel microspheres. Therefore, the microspheres can form reversible connections through hydrogen bonds, which is similar to the "self-cross-linking" effect. That is, the obtained plugging agent has a water-soluble polymer with a large number of hydroxyl groups as the main chain, and through free radical graft polymerization, the supramolecular special functional groups are grafted to the polymer side chains to synthesize a water-soluble polymer with an ordered supramolecular structure and a grid structure at a certain temperature. The present invention utilizes the uniqueness of supramolecular chemical materials and the strong interaction with the leakage formation to increase the plugging effect.

[0026] 2. The micro-nano gel plugging agent of the present invention is based on supramolecular chemistry theory, and special functional groups are connected to macromolecules. These special functional groups form an ordered supramolecular structure, which can quickly form a grid structure, cement the surrounding medium into a solid whole in the leakage layer, and use chemical plugging agents to inject into the leakage layer to form a gel to block the leakage channel. This plugging slurry has a low density, a large adjustment range of solidification time, a strong filtration ability of the slurry, and the filtrate can also solidify, which can block the microporous leakage channel. The plastic chips drilled after plugging have no adverse effects on the performance of the drilling fluid. The plastic plugging body solidified under the bottom hole conditions has high strength and good stability.

[0027] 3. The micro-nano gel plugging agent obtained by the present invention can withstand temperatures up to 150°C and pressures up to 7.5MPa.

[0028] 4. The raw materials used in the present invention can be purchased on the market, and the sources are wide and sufficient. The preparation method is simple, the on-site construction is convenient, it is not affected by temperature, the construction risk is greatly reduced, and it is easy to promote and apply on a large scale. After the configuration is completed, the plugging slurry has a low density, so the retention is high. At the same time, it has a special effect on the water-containing leakage layer.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other design solutions and drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The plugging agent solution used in Test Example 1, wherein: Figure 1 (a) is 1# plugging agent solution; Figure 1 (b) is 2# plugging agent solution;

[0032] Figure 2 The plugging agent solution used in Test Example 2, wherein: Figure 2 (a) is 3# plugging agent solution; Figure 2 (b) is the 4# plugging agent solution formed after the micro-nano gel plugging agent is allowed to stand at 90°C for 6 hours to gel;

[0033] Figure 3 This is the result of laser particle size analysis of micro-nano gel plugging agent.

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0036] An embodiment of the present invention provides a method for preparing a micro-nano gel plugging agent, comprising the following steps:

[0037] S1, mixing white oil and emulsifier to obtain mixed solution 1;

[0038] S2, after mixing water, monomer and cross-linking agent evenly, adding initiator, and mixing evenly again to obtain mixed solution 2;

[0039] S3, under a nitrogen atmosphere, mixing the mixed solution 2 and the mixed solution 1, raising the temperature to 55-65° C., reacting for 1-2 hours, to obtain a primary polymerization product;

[0040] S4, dissolving polyvinyl alcohol and chitosan in water, adding them to the above-mentioned primary polymerization product, heating to 65-75° C., reacting for 12-36 hours, filtering, separating, purifying and drying to obtain a micro-nano gel plugging agent.

[0041] The micro-nano gel plugging agent provided by the embodiment of the present invention first uses acrylamide and a cross-linking agent to perform reverse emulsion polymerization to form cross-linked microspheres, and then uses polyvinyl alcohol and chitosan to modify the surface of the microspheres. Since polyvinyl alcohol and chitosan are both macromolecules with a large number of hydroxyl groups on the surface, a large number of hydrogen bonds are added to the surface of the gel microspheres by wrapping and modifying the surface of the gel microspheres. That is, the obtained plugging agent has a water-soluble polymer with a large number of hydroxyl groups as the main chain, and through free radical graft polymerization, the special functional groups of the supramolecular are grafted to the side chains of the polymer to synthesize a water-soluble polymer with an ordered supramolecular structure and a grid structure at a certain temperature. The present invention utilizes the unique structure of supramolecular chemical materials to quickly form a grid structure, cement the surrounding medium into a solid whole in the leakage layer, and further utilizes the strong interaction with the leakage formation to increase the plugging effect.

[0042] In one embodiment of the present invention, further, in step S1, the mass ratio of white oil to emulsifier is 1:(1-2). The emulsifier is a Span emulsifier, such as Span 80.

[0043] In one embodiment of the present invention, in step 2), the mass ratio of distilled water, acrylamide, and N,N′-methylenebisacrylamide is 10-20:10-20:0.2-1; wherein the mass ratio of white oil to distilled water is 1:10-20.

[0044] In one embodiment of the present invention, further, in step S2, the mass ratio of water, monomer, and crosslinking agent is (10-20): (10-20): (0.2-1). Further, the monomer is acrylamide, the crosslinking agent is selected from at least one of divinylbenzene, N,N′-methylenebisacrylamide, N,N′-methylenebismethacrylamide, polyethylene glycol diacrylate, and pentaerythritol triacrylate, preferably N,N′-methylenebisacrylamide; the initiator is any one of ammonium persulfate, potassium persulfate, and sodium persulfate.

[0045] In a preferred embodiment of the present invention, the amount of initiator added is 1‰ to 2‰ of the monomer mass.

[0046] In a preferred embodiment of the present invention, the mass ratio of the white oil in step S1 to the water in step S2 is 1:(10-20).

[0047] In one embodiment of the present invention, in step S4, the mass ratio of polyvinyl alcohol, chitosan and water is (1-3):(0.5-1):1.

[0048] In a preferred embodiment of the present invention, the molecular weight of polyvinyl alcohol is 25,000 to 35,000. It should be further explained that polyvinyl alcohol with a molecular weight that is too low or too high is not suitable. A polyvinyl alcohol with a molecular weight lower than 25,000 will result in a plugging agent with too low viscosity and poor plugging effect, and a polyvinyl alcohol with a molecular weight higher than 35,000 will result in a plugging agent with too high viscosity and difficulty in flowing.

[0049] An embodiment of the present invention also provides a micro-nano gel plugging agent prepared by any of the above preparation methods. The particle size of the prepared micro-nano gel plugging agent is measured by a laser particle size analyzer, and the particle size of the micro-nano gel plugging agent is measured to be 0.5 microns to 200 microns. Figure 3 shown.

[0050] An embodiment of the present invention further provides a micro-nano gel plugging agent solution, including the micro-nano gel plugging agent prepared by any of the above preparation methods or any of the above micro-nano gel plugging agents. The micro-nano gel plugging agent solution can be directly used for plugging pores.

[0051] In one embodiment of the present invention, the micro-nano gel plugging agent solution further includes a structural agent. For large-pore formations, an appropriate amount of structural agent is added to the supramolecular gel plugging solution, and the rigid plugging material of the structural agent is used to form a supporting skeleton structure in the gel network system. When the system is subjected to force, the inorganic skeleton material can make the entire system bear stress more evenly, which can improve the strength of the gel, making it possible for the gel to plug large cracks.

[0052] In one embodiment of the present invention, the structural agent is a mixture of rigid particles, deformable particles, and mineral fibers. Among them, the rigid particles are mainly particles with hardness, specifically quartz sand, walnut shells, shell powder, etc. The deformable particles are mainly particles that can expand and soften, specifically rubber particles. Mineral fibers are mainly various mineral fibers, specifically silicon dioxide, etc. The rigid plugging material of the structural agent is used to form a supporting skeleton structure in the gel network system, so that when the system is subjected to force, the stress can be evenly distributed through the inorganic skeleton material, thereby improving the strength of the gel. Preferably, the mass ratio of rigid particles, deformable particles, and mineral fibers is (45-55): (25-35): (15-25).

[0053] In one embodiment of the present invention, the micro-nano gel plugging agent solution further comprises water, which is used to adjust the concentration of the micro-nano gel plugging agent solution as required.

[0054] The present invention will be described in detail below with reference to embodiments.

[0055] Example 1

[0056] This embodiment provides a method for preparing a micro-nano gel plugging agent, comprising the following steps:

[0057] S1. Measure 3g 3# white oil and 6g emulsifier Span 80 and add them to a three-necked flask and stir to obtain a mixed solution;

[0058] S2. Measure 60 g of distilled water, add 60 g of acrylamide (monomer), 6 g of N, N′-methylenebisacrylamide (cross-linking agent), and 0.12 g of potassium persulfate and stir evenly to obtain a mixed solution II;

[0059] S3. The mixed solution II was passed through a constant pressure dropping funnel and added to the mixed solution I in the three-necked flask under stirring, stirred evenly for 30 min, while nitrogen was passed for 30 min to exclude oxygen, the temperature was raised to 60 ° C, and the reaction was carried out for 1 h to obtain an initial polymerization product;

[0060] S4. Dissolve 1.5g polyvinyl alcohol (molecular weight 35,000) and 0.6g chitosan in 1ml distilled water, add into the initial polymerization product in the three-necked flask through a constant pressure dropping funnel, raise the temperature to 70°C, react for 24h, add excess ethanol to the product after the reaction is completed, and then filter, separate, purify and dry to obtain the micro-nano gel plugging agent.

[0061] Example 2

[0062] This embodiment provides a method for preparing a micro-nano gel plugging agent, comprising the following steps:

[0063] S1. Measure 6g 3# white oil and 6g emulsifier Span 80 and add them to a three-necked flask and stir to obtain a mixed solution;

[0064] S2. Measure 60 g of distilled water, add 60 g of acrylamide (monomer), 1.2 g of N, N′-methylenebisacrylamide (cross-linking agent), and 0.1 g of potassium persulfate and stir to obtain a mixed solution II;

[0065] S3. The mixed solution II was passed through a constant pressure dropping funnel and added to the mixed solution I in the three-necked flask under stirring, stirred evenly for 30 min, while nitrogen was passed for 30 min to exclude oxygen, the temperature was raised to 60 ° C, and the reaction was carried out for 1 h to obtain an initial polymerization product;

[0066] S4. Dissolve 1.2g polyvinyl alcohol (molecular weight 35,000) and 0.68g chitosan in 1ml distilled water, add into the initial polymerization product in the three-necked flask through a constant pressure dropping funnel, raise the temperature to 70°C, react for 24h, add excess ethanol to the product after the reaction is completed, and then filter, separate, purify and dry to obtain the micro-nano gel plugging agent.

[0067] Test Example 1

[0068] 1# and 2# plugging agent solutions were prepared respectively. Specifically, 1# plugging agent solution included: 300ml clean water + 8% structuring agent; 2# plugging agent solution included: 300ml clean water + 8% structuring agent + 2% micro-nano gel plugging agent obtained in Example 1; wherein the structuring agent was a mixture of rigid particle quartz sand, variable particle rubber particles, and mineral fiber silica in a mass ratio of 50:30:20.

[0069] Then pour the 1# and 2# plugging agent solutions onto the sand bed in the 71-type water loss meter, let it stand at 90℃ for 16 hours, and measure the instantaneous filtration loss under different pressures to investigate the gelation of the plugging agent. Figure 1 .

[0070] The gel plugging condition is reflected by recording the filtration loss of sand beds with different pores at different pressures for 10 minutes. As shown in Table 1:

[0071] Table 1 Performance evaluation of plugging agent solution (filtration loss / mL)

[0072]

[0073] Note: The amount of quartz sand is 100g and the experimental temperature is 90℃.

[0074] Test Example 2

[0075] 3# and 4# plugging agent solutions are respectively prepared. Specifically, 3# plugging agent solution includes: 300ml of clean water + 2% of the micro-nano gel plugging agent obtained in Example 2; 4# plugging agent solution includes: 300ml of clean water + 2% of the micro-nano gel plugging agent obtained in Example 2 + 18% of a structural agent; wherein the structural agent is a mixture of rigid particle quartz sand, variable particle rubber particles, and mineral fiber silica in a mass ratio of 50:30:20.

[0076] Then pour the 3# and 4# plugging agent solutions onto the sand bed in the 71-type water loss meter, let it stand at 90℃ for 16 hours, and measure the instantaneous filtration loss under different pressures to investigate the gelation of the plugging agent. Figure 2 .

[0077] The plugging condition of the gel is reflected by recording the 10-minute sand bed filtration loss under different pressures, as shown in the following table:

[0078] Table 2 Performance evaluation of plugging agent solution (filtration loss / mL)

[0079]

[0080] Note: The amount of quartz sand is 100g and the experimental temperature is 90℃.

[0081] From the experimental data in Table 1 and Table 2, it can be seen that the use of supramolecular micro-nano gel plugging solution to plug the sand bed can form a gel with a certain viscosity and elasticity after standing for 16 hours at 90°C. The higher the concentration, the greater the strength of the formed colloid, the smaller the formation pores, and the higher the pressure. At a certain temperature, as time goes by, the greater the strength of the formed gel, the better the plugging effect on the formation pores and cracks. The plugging agent has certain shear thinning and viscoelasticity, the time for forming the gel is adjustable, and the particle size can be adjusted according to the situation of the leaking layer to achieve the plugging effect.

[0082] Supramolecular gel solution can plug formations with larger pores and can withstand a pressure of up to 7.5MPa. For large-pore formations, an appropriate amount of structural agent is added to the supramolecular gel plugging solution, and the rigid plugging material of the structural agent is used to form a supporting skeleton structure in the gel network system. When the system is subjected to force, the inorganic skeleton material can make the entire system bear stress more evenly, which can improve the strength of the gel and make it possible for the gel to plug large cracks. After the supramolecular gel plugging solution is gelled, the system can be matched with graded rigid filling particles to plug formations with pores of about 1.5mm.

[0083] Field application experiment

[0084] The present invention applies the micro-nano gel plugging agent plugging technology to 8 wells (Su 20-6-11N, Su 36-5-9H2, Muping 15-20, Anping 39-25, Anping 31-17, Anping 39-25, Su 54-23-111, Yu 43-2zH3 wells) in Changqing block. Before construction, the 8 wells had a total of 46 leakages. The micro-nano plugging gel plugging technology was successfully plugged after 9 constructions. The one-time plugging success rate reached 88.9%, and the average leakage reduction rate of the applied well section reached 95%. The plugging slurry has high strength and good field adaptability, and no re-leakage occurs during the subsequent drilling process. It has little impact on the performance of the drilling fluid, and has laid a good technical foundation for the on-site plugging application in the Changqing area. It was applied to 7 wells in Yichuan, Qingyang, and Sulige blocks, with a one-time success rate of 100%, all of which met the design requirements, without repeated leakage and affecting the cementing quality. The micro-nano gel plugging agent increases the flow resistance in the leakage channel, and finally achieves a balance among the flow resistance, formation pressure and well pressure.

[0085] It can be seen that the micro-nano gel plugging agent obtained by the present invention solves the technical problems that the plugging agent cannot stay in the leaking layer, is easily diluted by water mixing, is difficult to stay and accumulate near the entrance of the leaking layer, and is difficult to block the leakage channel. At the same time, a new pressure plugging technology that adapts to and meets the needs of plugging different types of leaking layers is created, which greatly improves the pressure bearing capacity of low-pressure formations.

[0086] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-nano gel plugging agent, characterized in that: The following steps are involved: S1, mixing white oil and emulsifier to obtain a mixed solution 1; the mass ratio of the white oil to the emulsifier is 1:(1-2); S2, after mixing water, monomer and cross-linking agent, add initiator, mix again to obtain mixed solution 2; the mass ratio of water, monomer and cross-linking agent is (10-20): (10-20): (0.2-1); the amount of initiator added is 1‰-2‰ of the mass of monomer; S3, under a nitrogen atmosphere, mixing the mixed solution 2 and the mixed solution 1, heating to 55-65° C., reacting for 1-2 hours, to obtain a primary polymerization product; S4, dissolving polyvinyl alcohol and chitosan in water, adding them to the above-mentioned primary polymerization product, and heating to 65-75°C, reacting for 12-36 hours, and then filtering, separating, purifying and drying the reaction product to obtain a micro-nano gel plugging agent; wherein the mass ratio of the polyvinyl alcohol, chitosan and water is (1-3): (0.5-1): 1; the molecular weight of the polyvinyl alcohol is 25,000-35,000.

2. The method for preparing the micro-nano gel plugging agent according to claim 1, characterized in that: In step S1, the emulsifier is a Span emulsifier.

3. The method for preparing the micro-nano gel plugging agent according to claim 1, characterized in that: The monomer is acrylamide, the crosslinking agent is selected from at least one of divinylbenzene, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, polyethylene glycol diacrylate, and pentaerythritol triacrylate; and the initiator is any one of ammonium persulfate, potassium persulfate, and sodium persulfate.

4. The method for preparing the micro-nano gel plugging agent according to claim 1, characterized in that: The mass ratio of the white oil in step S1 to the water in step S2 is 1:(10-20).

5. A micro-nano gel plugging agent, characterized in that: The micro-nano gel plugging agent is prepared according to the preparation method of any one of claims 1 to 4.

6. The micro-nano gel plugging agent according to claim 5, characterized in that: The particle size of the micro-nano gel plugging agent is 0.5 micron to 200 microns.

7. A micro-nano gel plugging slurry, comprising at least the micro-nano gel plugging agent prepared by the preparation method of the micro-nano gel plugging agent according to any one of claims 1 to 6, characterized in that: The invention also comprises a structural agent, the dosage of which is 8-18% of the mass of the micro-nano gel plugging agent.

8. The micro-nano gel plugging slurry according to claim 7, characterized in that: The micro-nano gel plugging slurry also includes water, and the amount of water used is determined by the concentration of the nano gel plugging liquid.

9. The micro-nano gel plugging slurry according to claim 7, characterized in that: The structural agent is formed by mixing rigid particles, variable particles and mineral fibers in a mass ratio of (45-55): (25-35): (15-25).

Citation Information

Patent Citations

  • Preparation method of plugging agent

    CN108893101A

  • Healing and leaking stoppage stability evaluation method of self-healing gel leaking stoppage material

    CN110929400A